Utilization of Actinomycetes to increase phosphate availability at different soil moisture conditions in Andisols Namanteran, North Sumatera - Alfikri, M Reza; Sabrina, T; Sahar, Asmarlaili (Jurnal Ilmu Pertanian, 2023)
The high phosphate retention in Andisols causes the availability of P to be low, can not be absorbed by plants. Actinomycetes are capable of solubilizing bound phosphates. This research aimed to identify Actinomycetes in Andisols Namanteran, assess their ability to increase phosphate availability, and understand how they work to increase phosphate availability in this soil. The research design used a factorial randomized block design with 2 factors; factor 1 was Actinomycetes isolate, consisting of A₀ = No Inoculant, A₁ = Inoculant A₁₃₂ (vegetable crops; 32 × 10⁸ CFU mL⁻¹), A₂ = A₄₆₈ (forest plants; 41 × 10⁸ CFU mL⁻¹), A₃ = A₄₅₈ (forest plant; 58 × 10⁸ CFUmL⁻¹), A₄ = A₄₇₁ (coffee plant; 35 × 10⁸ CFU mL⁻¹), A₅ = A₄₅₉ (forest plant; 63 × 10⁸ CFU mL⁻¹), A₆ = A₃₂₁ (hibiscus plant; 37 × 10⁸ CFU mL⁻¹), and A₇ = A₃₅₆ (vegetable plant; 33 × 10⁸ CFU mL⁻¹), and factor 2 was soil water content, consisting of K₁ = 50%, K₂ = 75% and K₃ = 100% of field capacity. The results showed that the availability of P in Andisols increased due to the application of Actinomycetes from 42.46 ppm to 159.20−266.60 ppm. The population of Actinomycetes in Actinomycetes treatment ranged from 27.33−31.58 × 10⁸ CFU mL⁻¹), with a soil pH of 4.41. Water content of 100% was the best in increasing soil pH and Actinomycetes population, but not having significant effects on the available P of the soil. The results of molecular identification of Actinomycetes that have the best potential in dissolving P include A₃>A₅>A₂>A₄>A₁.